Experimently Induced Torsion Of Spleen and ITs Treatment In Canines - Mohindar Sing Bhadwal (Department of Surgery, College of Veterinary and Animal Science, 1988)
Eighteen apparently healthy dogs of either sex, aged one to five years and weighing 10-15 kg were used for the study. All the dogs were dewormed and examined for the presence of blood parasites if any. They were housed separately in cages under identical conditions of feeding and management and kept under observation for 10 days before the experiments.